2015
DOI: 10.1021/acs.analchem.5b00873
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic Platform for Studying Chemotaxis of Adhesive Cells Revealed a Gradient-Dependent Migration and Acceleration of Cancer Stem Cells

Abstract: Recent studies reveal that solid tumors consist of heterogeneous cells with distinct phenotypes and functions. However, it is unclear how different subtypes of cancer cells migrate under chemotaxis. Here, we developed a microfluidic device capable of generating multiple stable gradients, culturing cells on-chip, and monitoring single cell migratory behavior. The microfluidic platform was used to study gradient-induced chemotaxis of lung cancer stem cell (LCSC) and differentiated LCSC (dLCSC) in real time. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 53 publications
0
28
0
1
Order By: Relevance
“…They are known to express a list of biomarkers, such as CD15 and CD20 (Detail information: http://www.celprogen.com/details.php?pid=6423). This cell line was briefly characterized as described in a previous report (Zou et al, ). Third generation LCSCs (P3) were used in this study, and dLCSCs originated from LCSCs after 12 passages (P13) in the culture with an obvious change in cell morphology.…”
Section: Methodsmentioning
confidence: 99%
“…They are known to express a list of biomarkers, such as CD15 and CD20 (Detail information: http://www.celprogen.com/details.php?pid=6423). This cell line was briefly characterized as described in a previous report (Zou et al, ). Third generation LCSCs (P3) were used in this study, and dLCSCs originated from LCSCs after 12 passages (P13) in the culture with an obvious change in cell morphology.…”
Section: Methodsmentioning
confidence: 99%
“…By observing cell behavior in these devices, it was found that different types of cancer cells may react differently to the same chemical stimuli. This dynamic response was regulated by the β-catenin dependent Wnt signaling pathway [202]. Most convection-based devices are gradient generators in which several specific chemical concentrations are generated by mixing the different amount of fluid.…”
Section: Chemical and Oxygen Gradientmentioning
confidence: 99%
“…16,24 The relatively large scale in microstructure and the isotropic nature restrict PCB masters to be used in molding replicas with precise structures. However, the precision degree of PCB masters reaches the requirements of a lot of microuidic applications, such as cell-based assays, [28][29][30][31] droplet formation and operations, 22,32 microbead based analyses 33 and the generation of concentration gradients. 23 In this study, the insufficient adhesion due to the surface roughness was solved by sealing two semi-cured PDMS replicas.…”
Section: Generation Of Pdms Replicas On Commoditized Pcb Mastersmentioning
confidence: 99%